2021
DOI: 10.3897/mycokeys.80.64435
|View full text |Cite
|
Sign up to set email alerts
|

Brahmaculus gen. nov. (Leotiomycetes, Chlorociboriaceae)

Abstract: A second genus in Chlorociboriaceae is described here as Brahmaculusgen. nov. Macroscopically distinctive, all species have bright yellow apothecia with several apothecial cups held on short branches at the tip of a long stipe. The genus is widely distributed across the Southern Hemisphere; the four new species described here include two from Chile (B. magellanicussp. nov., B. osornoensissp. nov.) and one each from New Zealand (B. moonlighticussp. nov.) and Australia (B. packhamiaesp. nov.). They differ from s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…Besides, the nal average standard deviation of the split frequencies in the BI analysis based on the combine of ITS and LSU was 0.008298. The topology of the multilocus ML tree was partly similar to the BI analysis and also to the previous study of Johnston et al (2021) and Li et al (2022). The two single-gene Bayesian phylogenetic trees and the two single-gene Maximum likelihood phylogenetic trees all con rmed our eight specimens in this study constituted four monophyletic lineages, which were distant from other known species of Chlorociboria.…”
Section: Phylogenetic Analysessupporting
confidence: 82%
See 3 more Smart Citations
“…Besides, the nal average standard deviation of the split frequencies in the BI analysis based on the combine of ITS and LSU was 0.008298. The topology of the multilocus ML tree was partly similar to the BI analysis and also to the previous study of Johnston et al (2021) and Li et al (2022). The two single-gene Bayesian phylogenetic trees and the two single-gene Maximum likelihood phylogenetic trees all con rmed our eight specimens in this study constituted four monophyletic lineages, which were distant from other known species of Chlorociboria.…”
Section: Phylogenetic Analysessupporting
confidence: 82%
“…These newly generated sequences and the reference sequences from previous research are shown in Table 1. Cenangium ferruginosum (TAAM 198451), Chlorencoelia torta (KUS-F 52256) and Heyderia abietis (OSC 60392) were designated as outgroup taxa following Johnston et al (2021). The dataset for each gene region was aligned using MAFFT 7.49, then was trimmed in TrimAl 1.3, the gapthreshold parameter of ITS was set to 0.6, and the gapthreshold parameter of LSU was set to 0.4 (Capella-Gutiérrez et al 2009; Katoh and Standley 2013).…”
Section: Phylogenetic Analysesmentioning
confidence: 99%
See 2 more Smart Citations